2016
DOI: 10.1007/s00167-016-4201-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinesiophobia and depression affect total knee arthroplasty outcome in a multivariate analysis of psychological and physical factors on 200 patients

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…In these patients, preoperative and postoperative psychological factors significantly influence recovery (Katz, ; Katz & Seltzer, ). Specifically, studies show elevated fear of movement or pain catastrophizing, and low self‐efficacy as factors associated with poor outcomes after spine surgery and total hip and knee replacement including lower physical functioning (Archer, Seebach, Mathis, Riley, & Wegener, ; Archer et al, ; Coronado, George, Devin, Wegener, & Archer, ; Filardo et al, ; Wylde, Dixon, & Blom, ) and higher pain ratings (Archer et al, ; Burns et al, ; Coronado et al, ; Filardo et al, ; Riddle, Wade, Jiranek, & Kong, ; Vissers et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, preoperative and postoperative psychological factors significantly influence recovery (Katz, ; Katz & Seltzer, ). Specifically, studies show elevated fear of movement or pain catastrophizing, and low self‐efficacy as factors associated with poor outcomes after spine surgery and total hip and knee replacement including lower physical functioning (Archer, Seebach, Mathis, Riley, & Wegener, ; Archer et al, ; Coronado, George, Devin, Wegener, & Archer, ; Filardo et al, ; Wylde, Dixon, & Blom, ) and higher pain ratings (Archer et al, ; Burns et al, ; Coronado et al, ; Filardo et al, ; Riddle, Wade, Jiranek, & Kong, ; Vissers et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has also highlighted that 60% of the increase in pain score could be related to the presence of kinesiophobia [21,22]. This was supported by findings from a large cohort study demonstrating that, independent from other psychological factors, kinesiophobia negatively influences the mental state, function and the ability to participate in social activities in patients with TKA [21]. This implies that kinesiophobia affects the biopsychosocial well-being of TKA patients.…”
Section: Introductionmentioning
confidence: 70%
“…For instance, kinesiophobia has already been associated with a reduced knee flexion range of motion among knee replacement patients [8,14]. Previous research has also highlighted that 60% of the increase in pain score could be related to the presence of kinesiophobia [21,22]. This was supported by findings from a large cohort study demonstrating that, independent from other psychological factors, kinesiophobia negatively influences the mental state, function and the ability to participate in social activities in patients with TKA [21].…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, Roaldsen et al 27 also reported that fear of moving may be used as a marker for the level of physical activity. Another study by Filardo et al 28 on 200 patients with total knee arthroplasty showed that kinesophobia was also significantly associated with depression, particularly when avoiding physical activity.…”
Section: Discussionmentioning
confidence: 98%